'Unprecedented step:' In first, Poland returns Nazi-looted Jewish property - Aderet, Ofer (Haaretz, 2026)
Last week, Poland officially returned to Greece 91 artifacts stolen from Greek Jews by the Nazis and stored in Poland
Poland
Keywords: Europe Jews; Greece; Holocaust; Nazis; Poland